2011
DOI: 10.1097/dcr.0b013e318232116b
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomical and Surgical Consequences of Right Colectomy for Cancer

Abstract: An early postoperative CT can show arterial stumps after right colectomy for cancer. These stumps appear to be significantly longer than presumed; implying a significant improvement potential when specimen size is concerned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 16 publications
3
28
2
Order By: Relevance
“…Our findings are similar to earlier studies that also found a much longer residual arterial stump length than would be expected [12,27].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings are similar to earlier studies that also found a much longer residual arterial stump length than would be expected [12,27].…”
Section: Discussionsupporting
confidence: 83%
“…This distance records the length of the main supplying vessel removed, which is known to be highly variable between individuals [10,11] and the technique cannot assess the length of the tumour feeding artery left behind inside the patient. A recent Norwegian study based on post-operative CT-scans following complications necessitating imaging demonstrated that a much longer stump of artery was left inside the patient than that expected [12]. With optimal CME surgery and high tie ligation we would expect the vessel to be no longer than 10 millimetres (mm).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, they found that a postoperative computed tomographic (CT) scan can visualize the arterial stumps and that these stumps appear to be significantly longer than previously anticipated, implying that there is a significant improvement potential when surgical D3 dissection techniques are applied. 16 …”
Section: Lymph Node Harvestmentioning
confidence: 99%
“…Similarly, recently published papers have shown promising results related to the new innovative techniques of D3 resection of the right hemicolon. 16,17 In our opinion, a tailored and individualized preoperative planning of surgery is needed, especially due to the significant anatomical variance in the D3 area.…”
Section: The Future Of Tailored Crc Treatmentmentioning
confidence: 99%
“…[4][5][6][7] Patients with transverse colon cancer were often excluded from previous randomized controlled trials because it was difficult to determine the appropriate extent of lymph node dissection, and because the technical difficulties depend on the identification and lymph node dissection around the middle colic vessels, which have a variable anatomy. [5][6][7][8][9] The recent development of multidetector computed tomography (MDCT) has made it possible to perform three-dimensional CT angiography (3DCTA). Many studies have shown that MDCT is an accurate modality for imaging the anatomy of visceral arteries and veins.…”
mentioning
confidence: 99%